Environmental Viability of Two Methods of Mechanized Forest Residues Management - Dubravko Horvat; Zdravko Pandur; Marijan Šušnjar; Stjepan Nikolić; Marko Zorić (Croatian Journal of Forest Engineering, 2011)
This paper describes the assessment of environmental viability of timber extraction by two vehicles – forwarder and tractor assembly of 1-m wood by two methods of mechanized forest residues management. In the first variant, the forwarder was first used for extracting industrial roundwood, and then for all the remaining parts of the tree as energy wood. The second method was the common practice, i.e. the forwarder was used for transporting industrial roundwood and large logs, and then in the second phase 1-m firewood was processed from the remaining part of the tree, and it was extracted by the tractor assembly. In the third phase, the prepared (bunched) biomass was extracted by the forwarder.Environmental viability of the forwarder and tractor assembly for 1-m firewood was analyzed based on CI*NGP–1 ratio, i.e. index that represents the ratio between soil bearing strength, as the soil characteristics, and nominal wheel load, as the vehicle characteristics, so that it has a clear physical sense. This factor has been chosen because it consists of values that can be measured relatively easily or calculated with the use of semi-empirical models. The obtained values were compared with the recommended limit values from EcoWood project, which were based on the allowed 10-cm depth of the wheel rut.The analysis showed that the reference wheel of the tractor assembly semitrailer was the most unfavorable and that no environmentally viable wood extraction can be expected from such a vehicle, but only economic mobility. This is why the use of a non-drive bogie axle is recommended for them.The wheels of the farming tractor have the most favorable indicators of environmental viability, and particularly so the front wheels, whose load gets considerably lower with the increase of the semitrailer load.The indicators of the forwarder are considerably better, and however in this case, too, for achieving an environmentally acceptable maneuverability, according to EcoWood classification, the soil must be very strong with the cone index between 700 kPa for ~50 % load and up to 900 kPa for the nominal load value.During measurement and analysis of results, great dispersion was observed of the measuring data of the soil cone index obtained by cone penetrometer, sampled on a relatively non-homogenous forest soil. Searching for an acceptable measurement procedure by cone penetrometer or the application of any other measuring method for the assessment of the soil bearing strength is a significant task of scientific research.The assessment of the skidder environmental viability will be a still greater challenge, because they are characterized by a considerably more complex travel dynamics than moving on slopes, dynamic redistribution of axle loads, achievement of tractive force, etc. This is also the opinion of Horvat et al. (2007) with the emphasis on the fact that with skidders it is also necessary to analyze the impact of the winched and skidded load on the soil.